Research and analysis of the effect between the power level and economy on the lead-based modular nuclear power reactor - Lei, Lou; Lianjie, Wang; Bingyan, Zhou; Chen, Zhao; Bin, Zhang; Mingyu, Yan; Ce, Zhang; Hongzhi, Xiang; Yun, Cai; Xingbo, Wang; Zifan, Zhao; Nan, Zhou; et al. (Frontiers in Energy Research, 2022)
The fast reactor is gradually being paid attention to in nuclear power due to a better breeding effect, and its economy is also directly followed. Due to the restriction of the core power density, the core power level is directly related to the volume of the core active area. When the power level and the volume of the core gradually increase, the mass of uranium and 235U in the core at the beginning of life will gradually increase on the basis of a critical uranium inventory. At the same time, due to the gradual increase in the breeding effect, the utilization rate of uranium resources at the end of life will gradually increase. Due to the characteristics of the large critical uranium mass and high breeding effect, the mass of uranium and 235U in the low power level core at the beginning of life cannot be further reduced because of the critical uranium inventory. The lifetime of the high power level core should be extended to use the wealthy reactivity of the core because of the improvement in the breeding effect. However, due to the requirements of the nuclear power refuel time and the limitation to fuel consumption, the breeding effect brought by the improvement in the core power level and the size of the active zone may be less effective. In this article, the power level and economy of lead-based modular nuclear power are analyzed, and the economy of different power level fast reactors with 2,000 EFPD lifetime such as 100 MWt, 300 MWt, 500 MWt, 700 MWt, and 1000 MWt thermal power is designed and analyzed. By analyzing the invention of uranium and 235U and the fuel utilization of different core schemes, the best economic analysis of the single reactor power of the current lead-based modular reactor is proposed and the foundation of the lead-based modular nuclear power is provided.